3D simulation assisted resection of giant hepatic mesenchymal hamartoma in children. Issue 1 (1st January 2017) - Zhao, Jing; Zhou, Xian-Jun; Zhu, Cheng-Zhan; Wu, Ying; Wei, Bin; Zhang, Gang; Hao, Xi-Wei; Zhang, Hong; Jiang, Zhong; Dong, Qian
Abstract: Objective: To evaluate the usefulness of Hisense Computer Assisted Surgery System (Hisense CAS) in pre-operative surgical planning and intra-operative navigation for resection of pediatric giant hepatic mesenchymal hamartoma (HMH). Methods: Five children with HMH underwent hepatectomy in our hospital. Pre-operative abdominal enhanced CT was performed for diagnosis and treatment planning. Using CT DICOM files, three-dimensional reconstruction was performed in three cases for operation planning and intra-operative navigation, with SID carrying out precise liver resection during the operation with Hisense CAS. Result: Two patients underwent right and left lobe hepatectomy, respectively, based only on enhanced CT. In 3 patients, by using the Hisense CAS system, three-dimensional reconstruction of the liver and tumors was successfully completed, and virtual hepatectomy performed successfully according to surgical plans. Hisense CAS could clearly and directly indicate the HMH location and shape, as well as its relationship with the intra-hepatic Glisson system, assisting safe hepatectomy. All five patients recovered well from surgery without any complications, and pathological examinations confirmed that all cases were HMH. No recurrence was observed during the follow-up period of 3 months to 5 years. Conclusion: Hisense CAS system is useful for preoperative planning and intra-operative navigation, assisting safer hepatectomy.